Connect with experts and get insightful answers on IDNLearn.com. Find the answers you need quickly and accurately with help from our knowledgeable and experienced experts.
Sagot :
To solve the equation [tex]\((2 \cos \theta - \sqrt{3})(2 \sin \theta - 1) = 0\)[/tex], we need to consider each factor separately and solve for [tex]\(\theta\)[/tex] within the interval [tex]\([0, 2\pi)\)[/tex].
### Factor 1: [tex]\(2 \cos \theta - \sqrt{3} = 0\)[/tex]
1. Set [tex]\(2 \cos \theta - \sqrt{3} = 0\)[/tex] and solve for [tex]\(\cos \theta\)[/tex].
[tex]\[ 2 \cos \theta = \sqrt{3} \][/tex]
[tex]\[ \cos \theta = \frac{\sqrt{3}}{2} \][/tex]
2. Determine the values of [tex]\(\theta\)[/tex] within the interval [tex]\([0, 2\pi)\)[/tex] where [tex]\(\cos \theta = \frac{\sqrt{3}}{2}\)[/tex].
[tex]\[ \cos \theta = \frac{\sqrt{3}}{2} \text{ at } \theta = \frac{\pi}{6}, \frac{11\pi}{6} \][/tex]
### Factor 2: [tex]\(2 \sin \theta - 1 = 0\)[/tex]
1. Set [tex]\(2 \sin \theta - 1 = 0\)[/tex] and solve for [tex]\(\sin \theta\)[/tex].
[tex]\[ 2 \sin \theta = 1 \][/tex]
[tex]\[ \sin \theta = \frac{1}{2} \][/tex]
2. Determine the values of [tex]\(\theta\)[/tex] within the interval [tex]\([0, 2\pi)\)[/tex] where [tex]\(\sin \theta = \frac{1}{2}\)[/tex].
[tex]\[ \sin \theta = \frac{1}{2} \text{ at } \theta = \frac{\pi}{6}, \frac{5\pi}{6} \][/tex]
### Combine Solutions
We combine the solutions from each factor and ensure they are within the interval [tex]\([0, 2\pi)\)[/tex].
#### Solutions from [tex]\(2 \cos \theta - \sqrt{3} = 0\)[/tex]:
[tex]\[ \theta = \frac{\pi}{6}, \frac{11\pi}{6} \][/tex]
#### Solutions from [tex]\(2 \sin \theta - 1 = 0\)[/tex]:
[tex]\[ \theta = \frac{\pi}{6}, \frac{5\pi}{6} \][/tex]
Combine these solutions into a single set and sort them:
[tex]\[ \theta = \frac{\pi}{6}, \frac{5\pi}{6}, \frac{11\pi}{6} \][/tex]
Thus, the final solutions to the equation [tex]\((2 \cos \theta - \sqrt{3})(2 \sin \theta - 1) = 0\)[/tex] in the interval [tex]\([0, 2\pi)\)[/tex] are:
[tex]\[ \theta = \frac{\pi}{6}, \frac{5\pi}{6}, \frac{11\pi}{6} \][/tex]
### Factor 1: [tex]\(2 \cos \theta - \sqrt{3} = 0\)[/tex]
1. Set [tex]\(2 \cos \theta - \sqrt{3} = 0\)[/tex] and solve for [tex]\(\cos \theta\)[/tex].
[tex]\[ 2 \cos \theta = \sqrt{3} \][/tex]
[tex]\[ \cos \theta = \frac{\sqrt{3}}{2} \][/tex]
2. Determine the values of [tex]\(\theta\)[/tex] within the interval [tex]\([0, 2\pi)\)[/tex] where [tex]\(\cos \theta = \frac{\sqrt{3}}{2}\)[/tex].
[tex]\[ \cos \theta = \frac{\sqrt{3}}{2} \text{ at } \theta = \frac{\pi}{6}, \frac{11\pi}{6} \][/tex]
### Factor 2: [tex]\(2 \sin \theta - 1 = 0\)[/tex]
1. Set [tex]\(2 \sin \theta - 1 = 0\)[/tex] and solve for [tex]\(\sin \theta\)[/tex].
[tex]\[ 2 \sin \theta = 1 \][/tex]
[tex]\[ \sin \theta = \frac{1}{2} \][/tex]
2. Determine the values of [tex]\(\theta\)[/tex] within the interval [tex]\([0, 2\pi)\)[/tex] where [tex]\(\sin \theta = \frac{1}{2}\)[/tex].
[tex]\[ \sin \theta = \frac{1}{2} \text{ at } \theta = \frac{\pi}{6}, \frac{5\pi}{6} \][/tex]
### Combine Solutions
We combine the solutions from each factor and ensure they are within the interval [tex]\([0, 2\pi)\)[/tex].
#### Solutions from [tex]\(2 \cos \theta - \sqrt{3} = 0\)[/tex]:
[tex]\[ \theta = \frac{\pi}{6}, \frac{11\pi}{6} \][/tex]
#### Solutions from [tex]\(2 \sin \theta - 1 = 0\)[/tex]:
[tex]\[ \theta = \frac{\pi}{6}, \frac{5\pi}{6} \][/tex]
Combine these solutions into a single set and sort them:
[tex]\[ \theta = \frac{\pi}{6}, \frac{5\pi}{6}, \frac{11\pi}{6} \][/tex]
Thus, the final solutions to the equation [tex]\((2 \cos \theta - \sqrt{3})(2 \sin \theta - 1) = 0\)[/tex] in the interval [tex]\([0, 2\pi)\)[/tex] are:
[tex]\[ \theta = \frac{\pi}{6}, \frac{5\pi}{6}, \frac{11\pi}{6} \][/tex]
Thank you for using this platform to share and learn. Keep asking and answering. We appreciate every contribution you make. Thank you for visiting IDNLearn.com. We’re here to provide dependable answers, so visit us again soon.